Photocatalytic Oxidation Of Chitosan And Its Derivatives And Phenol By Immobilized TiO2 Bilayer Assemblage Systems Under Visible Light - Al-Taie, Ali Hadi Jawad (2011)
Simple bilayer systems consisting of TiO2 as a top layer and chitosan (CS), cross-linked chitosan-glutaraldehyde (CS-GLA) and chitosan-epichlorohydrin (CS-ECH) as sub-layers were successfully fabricated and immobilized onto a glass plate. The deposition and adhesive properties of TiO2 were improved by adding organic binders like epoxidized natural rubber (ENR50) and phenol-formaldehyde resin (PF) in the coating formulation. Exposing these bilayer systems in aerated aqueous solution to 45-W fluorescent lamp caused significant changes in content of both ENR50 and PF of TiO2 top layer, in addition to the remarkable physico-chemical changes of CS, CS-GLA and CS-ECH sub-layers.